Study of utilization of petrol engine equipped with exhaust gas recirculation (EGR) and catalytic converter to reduce consumption and NOx emission - De Araújo Porto, Fernando Silva; Bailona, Baltazar Agenor; Camargo, José Rui; Balestieri, José Antônio Perrella [UNESP]; Lukasiunas, Marco Donizeti (SAE International, 2006)
Study of consumption rate and gaseous pollutant emission from engine tests simulating real work conditions, using spark point manually controlled and exhaust gas recirculation (EGR) in diverse proportion levels. The objective of this work is to re-examine the potential of the EGR conception, a well-known method of combustion control, employed together electronic fuel injection and three-way catalytic converter closed-loop control at a spark ignition engine, verifying the performance characteristics and technical availability of this conception to improve pollution control, fuel economy at low torque drive condition and to improve the engine exhaust components useful life. The pollutant emissions and consumption levels under operational conditions simulations were analysed and compared with the expected by concerning theory and real tests performed by EGR equipped engines by factory. Copyright © 2006 Society of Automotive Engineers, Inc.
Keywords: Closed-loop control; Combustion control; Consumption levels; Consumption rates; Electronic fuel injections; Engine test; Gaseous pollutants; NOx emissions; Operational conditions; Performance characteristics; Petrol engine; Pollutant emission; Three way catalytic converter; Useful life; Work condition; Catalytic converters; Fog; Fuel economy; Exhaust gas recirculation